Perioperative and oncological outcomes of radical prostatectomy for high‐risk prostate cancer in the UK: an analysis of surgeon‐reported data. (10th June 2019) - Aning, Jonathan J.; Reilly, Gavin S.; Fowler, Sarah; Challacombe, Ben; McGrath, John S.; Sooriakumaran, Prasanna; ,
Abstract : Objectives: To analyse the perioperative and oncological outcomes of all radical prostatectomies (RPs) performed for high‐risk prostate cancer in the British Association of Urological Surgeons (BAUS) national registry from 2014 to 2015. Patients and Methods: We identified and analysed outcomes of all RPs performed for high‐risk prostate cancer (clinical stage >T2 and/or biopsy Gleason grade >7 and/or preoperative prostate‐specific antigen level ≥20 ng/mL) in the national registry for 2014 and 2015. Surgeon reporting of data was mandated during this period. Institution and individual surgeon volume–outcome relationships were assessed. Results: In total, 3671/13 947 (26.3%) patients underwent RP for high‐risk prostate cancer over the 2‐year period. Robot‐assisted RP was the most prevalent approach (60.7%). In all, 39% of men received an extended pelvic lymph node dissection (LND), but over one‐third (33.8%) had no LND. Minimally invasive techniques were associated with a significantly shorter length of stay. The reported rates of Clavien–Dindo ≥III complications within the dataset were low (2.0%), regardless of surgical modality or surgeon volume. No statistically significant surgeon volume–outcome relationships were identified when surgeon volume was stratified into tertiles. Conclusion: RP for high‐risk prostate cancer in the UK appears safe, regardless of modality used or surgeon volume. No clear evidence that surgeon volume impacts on early perioperative outcomes was seen. Quality assurance of the surgeon‐reported BAUS dataset is now required to drive quality improvement in national practice.